The effect of feedback assessment and learning motivation on students’ performance - Desrita Yanti; Friyatmi Friyatmi (Global Econedu, 2026)
This study examined the direct effect of feedback assessment on student performance and its indirect effect through learning motivation among vocational high school students. A quantitative causal research design was employed involving 299 students selected through proportional simple random sampling from two public vocational high schools in Kecamatan IV Jurai, Indonesia. Data on feedback assessment and learning motivation were collected using validated Likert-scale questionnaires, while student performance was measured using mid-semester examination scores. Data were analyzed using descriptive statistics and path analysis. Feedback assessment significantly influenced learning motivation (β = 0.686, p < 0.001), whereas its direct effect on student performance was not significant (β = 0.002, p = 0.976). Learning motivation significantly predicted student performance (β = 0.197, p = 0.013) and mediated the relationship between feedback assessment and student performance. Learning motivation is a key mechanism through which feedback assessment contributes to improved academic performance in vocational education